Time Perspective and Psychological Problems Among Adolescents Affected By Violent Conflict In Indonesia - Turnip, Sherly Saragih (Makara Human Behavior Studies in Asia, 2010)
Conflicts and wars in several areas in Indonesia have caused a large number of Internally Displaced Persons (IDPs). IDPs adolescents are a vulnerable group for developing psychological problems. There was a concern about the form of time perspective that these adolescents have and its relationship with the occurrence of psychological problems in the future. However, there is a lack of studies of internally displaced persons that assess the relationship between psychological distress and time perspective in low income countries. The study aim was to assess psychological status and time perspective of adolescents who were affected by violent conflict in Indonesia. Cross sectional community based study. Questionnaires were used to obtain data from 129 adolescents whose lives were affected by violent conflict, both displaced and non-displaced. Subjects were selected by simple random sampling. Displaced adolescents were present-past oriented, while non-displaced adolescents were future oriented. Displaced adolescents had more difficulties compared to non-displaced adolescents, especially in emotional symptoms. Factors like migration status, gender and religion have partial significance toward time dominance and psychological problems. There is a significant association between time perspective and psychological problems in which present-past oriented adolescents had greater difficulties than future oriented adolescents. The most common problem was emotional symptoms, especially anxiety problems.